Message - Mgbahurike, Dr. Amaka A. (Universal Journal of Pharmaceutical Research, 2018)
Researches, generally, are meant to play vital role in development, improvement of our environment and our collective well-being. Knowledge acquired through research, when disseminated widely impacts positively in many areas. Universal Journal of Pharmaceutical Research, (UJPR), since its inception has gradually and still is impacting knowledge globally through its wide dissemination of research studies. UJPR has a good citation, highly indexed and abstracted in over 40 well known indexing services. Some of these indexing services include Directory of Science, Academic keys, American Chemical Society, Base, CAS, COSMAS, ROAD, and so many more. UJPR gather academic professionals, editorial board members, and researchers from across the globe. The editorial board members cut across many countries like India, China, Egypt, Bangladesh, Nigeria, Switzerland, Spain, Saudi Arabia, United Kingdom, South Africa, Iraq and Brazil. This congregation of national and international professionals adds value to the guidance and scientific suggestions which encourages cross -fertilization of ideas and knowledge. UJPR has successfully published articles from many countries including Nigeria, Yemen, Cameroon, Egypt, China, Pakistan, Iran, Iraq, Malaysia, Sudan, Bangladesh, Saudi Arabia, USA, West Indies, etc. The prompt response by UJPR to submitted articles is an added plus to the quality of the editorial board and the reviewers. The sheer volume of publications and the spread as well as congregation of prominent intellectuals have placed UJPR among the prestigious journals, suitable for many researchers and Faculties to disseminate their works. I congratulate all the researchers who contributed in this issue of the journal and encourage younger and eminent researchers for the next issue. As UJPR continues to climb to get to the top of the mountain, nurturing its dreams, until the goal is achieved, I encourage the flag to keep flying.